The influence of work motivation on employee performance (Lighthouse Publishing, 2022)
In order to improve the quality of human capabilities and advance organizational goals, existing human resources must be developed. When people perform well, organizational goals can be achieved as much as possible. Employees must be given an organized and efficient direction in order to perform well. The purpose of this systematic literature review is to synthesize some of the literature relating to the influence of work motivation on employee performance. The preparation of this study uses the Preferred Reporting Item for Systematic Review and Meta Analysis method from several studies that have a relationship with the influence of work motivation on employee performance. Data collection uses the Pupuation, Intervention, Comparison, and Outcome methods using two accesses, namely Science Direct and Cambridge e Journals. A total of 147 data were filtered with data inclusion criteria so that 30 data were obtained according to the eligibility standard. Obtained from the results of this study that work motivation greatly influences a person's performance, both intrinsic and extrinsic motivation as well as intrinsic and intrinsic motivation simultaneously. The more an employee is motivated, the more productive his performance will be. In addition, this study only uses 2 variables and it is suggested to future researchers to use more than 2 variables so that their research can cover employee performance more broadly.